Kandungan Senyawa Saponin pada Daun, Batang dan Umbi Tanaman Binahong (Anredera cordifolia (Ten) Steenis) - Hasbullah, Umar Hafidz Asyâari (Universitas Muhammadiyah Yogyakarta, 2016)
Saponin is one of the bioactive compounds present in plants. Saponin has the benefit of human health. Indonesian has been used binahong (Anredera cordifolia (Ten) Steenis) to medicine. However, empirical evidence regarding the content of saponin in binahong not been revealed. This study aims to determine the qualitative and quantitative content of saponins in plants binahong. The results showed that base on Tin Layer Chromatography (TLC) analysis, saponin content in the leaves, stems and tubers binahong both young and old were positive. Quantification results the young leaves, old leaves, young stems, old stems, young tubers and old tubers: 1.37ìg/mg, 2.36ìg/mg, 1.89ìg/mg, 1.2ìg/mg, 1.55ìg/mg and 1.35ìg/mg respectively.